1
$\begingroup$

This question is mostly out of curiosity, but I hope that the answer will advance my understanding of the trigonometric function. While playing around with trigonometric functions on WolframAlpha I stumbled upon this $$\cot(2\arctan(Ax))=\frac{1-(Ax)^2}{2Ax}$$ I suspect that one could prove this using the complex forms of the trigonometric functions $\sin(z) = \dfrac{e^{iz}-e^{-iz}}{2i}$ but I myself do not know the complex form of $\arctan$ so I am unable to do this.

Is there some nice geometric or algebraic proof that explains why $\cot(2\arctan(Ax))=\frac{1-(Ax)^2}{2Ax}$? Or maybe, is WolframAlpha wrong and does $\cot(2\arctan(Ax))$ just happen to be very close to $\frac{1-(Ax)^2}{2Ax}$?

$\endgroup$
2
$\begingroup$

We have the following fundamental trigonometric identity: $$\tan2t=\frac{2\tan t}{1-\tan^2t}$$ Take reciprocal on both sides: $$\frac1{\tan2t}=\frac{1-\tan^2t}{2\tan t}$$ Now substitute $t=\arctan Ax$ to get the identity in the question. ($\cot x\equiv\frac1{\tan x}$.)

$\endgroup$
0
$\begingroup$

Use the fact that $\cot \theta=\dfrac{1}{\tan \theta}$

And the double angle formula for tangent:

$\tan 2\theta=\dfrac{2\tan \theta}{1-\tan^2 \theta}$

Lastly, before I confuse myself let's do some replacement.

$\tan^{-1} Ax=z$

$Ax=\tan z$

Hence the full thing is:

$=\left(\tan (2\tan^{-1} Ax) \right)^{-1}$

$=(\tan 2z)^{-1}= \dfrac{1-\tan^2 z}{2\tan z}$

All good now, I hope.

Substitute $\tan z$ for $Ax$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.